(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of the research is to prove the implementation of the concept of sales growth, firm size, profitability, and Earning Per Share (EPS) in manufacturing companies listed on the Indonesia Stock Exchange. Research method using data analysis techniques using path analysis, variable independent used more than one variable and among independent variables, there is a causal relationship. The results of the study found sales growth affects profitability in manufacturing companies, larger companies will tend to have higher profitability, profitability affects earnings per share. This research proves the concept of sales growth, size, profitability, and EPS occurs in manufacturing companies listed on the Indonesia Stock Exchange.